On the design of Phase Change Materials based thermal management systems for electronics cooling. (September 2021) - Righetti, Giulia; Zilio, Claudio; Doretti, Luca; Longo, Giovanni A.; Mancin, Simone
Highlights: The design of latent heat storages for electronics cooling application is studied. The effects of different operating conditions are investigated. The use of 3D periodic structures is discussed during intermittent operations. The thermal conductivity maximization cannot be considered the only design objective. Abstract: This work aims at explaining the effect of the operating conditions on the performance of passive electronic thermal management systems based on Phase Change Materials. The low thermal conductivity of the Phase Change Materials is usually felt as one of their major limitations that hinders the effective heat transfer capability of the whole passive system. However, the present study experimentally demonstrates that the real improvement due to the use of enhanced heat transfer surfaces depends upon the operating conditions. The experimental tests were run on a latent thermal management system based on a paraffin wax with a 70 °C phase change temperature embedded in two different samples: an aluminum 3D pyramidal periodic structure having a porosity of 0.95 and a cell dimension of 10 mm realized via additive manufacturing, and an empty sample used as reference. The system was experimentally tested under several working conditions to simulate the real operation of an electronic device, including complete melting/solidification cycle and intermittent operations at different ambient temperatures, in natural and forced convection. The main outcome of the present study is that, when considering the junction temperature, the use of the enhanced surface does not always lead to an improvement of the heat transfer performance especially during fast intermittent operations and thus the maximum effective thermal conductivity cannot be always considered the main design objective. A novel integrated design approach should include the properties of the Phase Change Material, the system requirements and the real operating conditions.